KEPEMIMPINAN DIGITAL KEPALA SEKOLAH DAN GURU DALAM MENGATASI KESENJANGAN KESIAPAN DIGITAL PESERTA DIDIK DI SMP NEGERI 1 MEULABOH - Dian Erlita (Jurnal Humaniora Pendidikan (JHP), 2025)
This study aims to analyze the effect of digital leadership of principals and teachers on students’ digital readiness in addressing the digital readiness gap. The research was conducted at SMP Negeri 1 Meulaboh using a quantitative approach through Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The sample consisted of 20 respondents, including teachers and students, selected using purposive sampling. The research instrument was a Likert-scale questionnaire that had been tested for validity and reliability. The results showed that digital leadership has a positive and significant effect on students’ digital readiness, with a path coefficient of 0.79, a t-statistic of 6.45, and a p-value of 0.000. The coefficient of determination (R²) of 0.62 indicates that digital leadership contributes 62% to students’ digital readiness. These findings confirm that effective digital leadership enhances students’ digital literacy, technological skills, and positive attitudes toward technology-based learning. Therefore, strengthening digital leadership is a key strategy in supporting technology-based educational transformation.